Environmental education as the foundation of environmental protection activities (Международный научный журнал «Инженер», 2026)
The article examines transport as a source of environmental pollution. It analyzes the educational processin environmental disciplines at foreign and domestic universities. The teaching methodology of the"Ecology" course is discussed with a focus on shaping an environmentally conscious worldview amongfuture transport industry specialists. The approach considers production-specific factors and aims tofoster student interest and creativity through extracurricular activities. Measures are proposed to furtherimprove environmental education by nurturing students' love for nature, respect for their chosenprofession, and a deep understanding of the goals of the "Ecology" discipline. These improvements areto be achieved through enhanced integration between educational institutions and industry.